2015
DOI: 10.3892/mmr.2015.3181
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10a silencing reverses cisplatin resistance in the A549/cisplatin human lung cancer cell line via the transforming growth factor-β/Smad2/STAT3/STAT5 pathway

Abstract: Abstract. Lung cancer is one of the primary causes of mortality worldwide and drug resistance is the key contributing factor which results in the failure of lung cancer chemotherapy. Previous studies have shown that microRNA (miR)-10a was involved in the reversal of cisplatin (DDP) resistance in numerous types of tumors; however, the underlying mechanism of action of this remains to be fully elucidated. In the present study, miR-10a silencing in human DDP-resistant lung cancer A549/DDP cells was demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…Sun et al [36] reported that miR-10a-5p may be a potential target for improving the effectiveness of lung cancer chemotherapy via regulation of the TGF-β/Smad2/ STAT3/STAT5 pathway. Previous published research has highlighted that miR-10a-5p was significantly markedly overexpressed and influenced the chemotherapy response in NPM1 mut AML, which may exert its biological properties in AML by interfering with the p53 machinery, which is partly regulated by MDM4 [13,14,30].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al [36] reported that miR-10a-5p may be a potential target for improving the effectiveness of lung cancer chemotherapy via regulation of the TGF-β/Smad2/ STAT3/STAT5 pathway. Previous published research has highlighted that miR-10a-5p was significantly markedly overexpressed and influenced the chemotherapy response in NPM1 mut AML, which may exert its biological properties in AML by interfering with the p53 machinery, which is partly regulated by MDM4 [13,14,30].…”
Section: Discussionmentioning
confidence: 99%
“…As one previous study show that down-regulated STAT3 expression can resulted in reduced β-catenin mRNA and protein levels [38], and another study reported that BAMBI knockdown can significantly decrease the expression of β-catenin mRNA and suppress metastasis of gastric cancer cells [39]. However, miR-10a silencing may reverses cisplatin resistance in human lung cancer cell line via the TGF-β/Smad2/STAT3/STAT5 pathway [40]. Thus, we speculate that miR-10a may indirectly affect the β-catenin mRNA expression by targeting STAT3 and/or BAMBI, and this will be further investigate in our future research.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of Let-7c sensitizes A549/DDP cells to CDDP by targeting ABCC2 [43]. Moreover, miR-10a, miR-106a and miR-134 can regulate different members of MDR to affect the responses of lung adenocarcinoma cells to CDDP [44][45][46].…”
Section: Mirnas Involved In Regulation Of Drug Transportsmentioning
confidence: 99%